Should I Stay or Should I Go? Sibling Effects in Household Formation - Ainhoa Aparicio Fenoll; Veruska Oppedisano (Institute for the Study of Labor (IZA), 2014)
In Southern Europe youngsters leave the parental home significantly later than in Northern Europe and United States. Policies have been implemented in Southern Europe to incentivize young adults to leave parental home earlier. Do peer effects among siblings amplify the effects of these policies? Estimating peer effects is challenging because of problems of reflection, endogenous group formation, and correlated unobservables. We overcome these issues in the context of a Spanish rental subsidy, exploiting the subsidy eligibility age threshold to analyse peer effects among siblings. Instrumental variable estimates show that peer effects among siblings are negative, and that the effect is explained by the presence of old or ill parents. Findings indicate that policy makers should target the household rather the individual, and combine policies for young adults together with policies for elderly.
Keywords: J1; H2; I3; 330; peer effects; conditional cash transfer; youth emancipation; living arrangements